Ukraine : Technical Assistance Report-Fiscal Decentralization and Legal Framework for Fiscal Risk Management and Medium-term Budgeting. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance paper on Ukraine reviews the results of the 2015 fiscal decentralization reform and the amendments to the Budget Code for implementation of certain Public Financial Management reforms. Several design issues are slowing the process of voluntary amalgamation of territorial communities and will lead to a proliferation of small units, with low potential for financial self-sufficiency. Achieving both an overall balance and a vertical fiscal balance, whereby own revenues cover basic expenditure responsibilities and dependence on State grants and subventions is minimized, would require a combination of changes to the revenue-sharing arrangements and expenditure assignments. There is no structured arrangement for ensuring a collaborative and coordinated approach in pursuing broad fiscal objectives and ensuring fiscal sustainability at all levels of government. The authorities should take steps to ensure an active and open dialogue between the different levels on the conduct of fiscal policy.